A review of bone marrow niche cellular spectrum - Sabry A Shoieb; Mohammad A Abdel Hafez; Alaa E Abd El-Hamid; Walaa Hamdy Ezz (SpringerOpen, 2019)
To perform a narrative review on the role of bone marrow (BM) niche in normal hematopoiesis. MEDLINE databases and Ovid database were searched. The search was performed on 10 October 2018 and included articles published from 2015 to 2018 in English language. The initial search presented 45 articles, which were included in the study. Hematopoietic stem cells which produce a variety of hematopoietic lineage cells throughout the life are located in a specialized microenvironment called the 'niche' in the BM where they are governed. Several types of cells in the BM have been suggested to contribute to hematopoietic stem cell niche activity.